The Influence of Price, Brand Image, and Service Quality on Customer Satisfaction (A Study on Consumers of PT Gemilang Cipta Abadi in South Jakarta) - Sukarno, Sukarno; Vildayanti, Rina Ayu (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the influence of price, brand image, and service quality on customer satisfaction in the context of PT Gemilang Cipta Abadi located in South Jakarta. The research adopts a quantitative approach using a purposive sampling technique to capture perceptions of customers through structured questionnaires. The analysis applies multiple linear regression to evaluate the significance of each independent variable toward the dependent construct. Findings demonstrate that price, brand image, and service quality positively and significantly affect customer satisfaction both individually and collectively. The results underscore the importance of implementing competitive pricing strategies, strengthening brand equity, and enhancing service quality dimensions such as tangibles, reliability, responsiveness, assurance, and empathy. These elements are shown to be decisive in shaping customer loyalty and long-term relationships. The implications highlight the necessity for managers to align marketing strategies with customer expectations to secure sustainable competitiveness in a dynamic business environment.